2021
DOI: 10.2174/1568026620666201102121606
|View full text |Cite
|
Sign up to set email alerts
|

4-Aryl-1,4-Dihydropyridines as Potential Enoyl-Acyl Carrier Protein Reductase Inhibitors: Antitubercular Activity and Molecular Docking Study

Abstract: Background: Tuberculosis remains one of the most deadly infectious diseases worldwide due to the emergence of multi-drug resistance (MDR) and extensively drug resistance (XDR) strains of Mycobacterium tuberculosis (MTB). Materials and Methods: Herein, the screening of a total of eight symmetrical 1,4-dihydropyridine (1,4-DHP) derivatives (4a-4h) was carried out for whole-cell anti-TB activity against the susceptible H37Rv and MDR strains of MTB. Results and Discussion: Most of the compounds exhibited mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Fiszer-Maliszewska and co-workers in 1985 observed that some DHPs inhibited the in vitro growth of antibiotic-resistant Mycobacterium tuberculosis strains at 3.1 mg/L ( Fiszer-Maliszewska et al, 1985 ). Since then, the antitubercular properties of other DHP derivatives have been reported by many other researchers ( Trivedi et al, 2011 ; Desai et al, 2015 ; Zandhaghighi et al, 2017 ; Venugopala et al, 2021 ). DHPs have been also evaluated as antimicrobials against other pathogenic bacteria including S. aureus ( Ceviz et al, 1997 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Nosrati et al, 2021 ), E. coli ( Murthy et al, 2012 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Pseudomonas aeruginosa ( Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Vibrio cholerae ( Lavanya et al, 2021 ) and Klebsiella pneumoniae ( Murthy et al, 2012 ); but also against parasites ( Núñez-Vergara et al, 1997 ; Palit and Ali, 2008 ; Reimao et al, 2010 ; Pollo et al, 2017 ; Jeddi et al, 2021 ) and fungi ( Chhillar et al, 2006 ; Jezikova et al, 2017 ; Ahamed et al, 2018 ).…”
Section: Discussionmentioning
confidence: 82%
“…Fiszer-Maliszewska and co-workers in 1985 observed that some DHPs inhibited the in vitro growth of antibiotic-resistant Mycobacterium tuberculosis strains at 3.1 mg/L ( Fiszer-Maliszewska et al, 1985 ). Since then, the antitubercular properties of other DHP derivatives have been reported by many other researchers ( Trivedi et al, 2011 ; Desai et al, 2015 ; Zandhaghighi et al, 2017 ; Venugopala et al, 2021 ). DHPs have been also evaluated as antimicrobials against other pathogenic bacteria including S. aureus ( Ceviz et al, 1997 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Nosrati et al, 2021 ), E. coli ( Murthy et al, 2012 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Pseudomonas aeruginosa ( Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Vibrio cholerae ( Lavanya et al, 2021 ) and Klebsiella pneumoniae ( Murthy et al, 2012 ); but also against parasites ( Núñez-Vergara et al, 1997 ; Palit and Ali, 2008 ; Reimao et al, 2010 ; Pollo et al, 2017 ; Jeddi et al, 2021 ) and fungi ( Chhillar et al, 2006 ; Jezikova et al, 2017 ; Ahamed et al, 2018 ).…”
Section: Discussionmentioning
confidence: 82%
“…Venugopala and co‐workers have reported 1,4‐dihydropyridine with MIC of 16 μg/mL and 128 μg/mL against H 37 Rv and MDR Mtb respectively (Figure 13). [60] Docking studies of this compound 30 against InhA (PDB IDs: 5G0S and 5G0 U) have shown good binding to InhA. Compound 30 was found safe without any toxicity up to 380 μg/mL through in vitro safety studies against the normal peripheral blood mononuclear cells.…”
Section: Introductionmentioning
confidence: 96%
“…[7] Compound E. TPMPA, is a selective antagonist of GABAC receptors, [8] and Compound F. GTS-21, is a nACh receptor agonist that is both orally active and selective for alpha-7 nicotinic acetylcholine (nACh). [9] THPs have also been comprehensively studied for their prospective pharmacological actions such as anticancer, [10][11] antidiabetic, [12] anti-neurotropic, [13] anti-tubercular, [14] bronchodilations, [15] larvicidal, [16] neuropeptide YY1 receptor antagonists, [17] neuroprotective, [18] platelet anti-aggregation, [19] anti-inflammatory, [20] mGluR1 antagonists, [21] antihypertensives, [22] antimicrobial, [23][24][25] antimycobacterial, [26] antifungal, [27] antimalarial [28] and anti-HIV [29] activities. Substituted tetrahydropyridines have been synthesized employing various catalysts like iodine, [30] bromodimethylsulfonium bromide, [31] glycolic acid, [32] vitamin B1, [33] lactic acid, [34] lanthanum nitrate, [35] nickel chloride hexahydrate, [36] sulfamic acid, [37] cyanuric chloride, [38] sodium dioctyl sulfosuccinate, [39] acetic acid, [40] tetrabutylammonium tribromide, [41] picric acid, [42] and thiourea dioxide.…”
Section: Introductionmentioning
confidence: 99%